Energy management of multiple renewable energies system - Ling, Ju Loong (2014)
Renewable energies are gaining popularity in the recent world due to the depletion of fossil fuel. Pollution due to emission of gases from burning of fuel also aids in the campaign of renewable energies. This study presents the energy management of multiply renewable energies system to output a steady power with no fluctuation regardless of the power drawn and the source availability. The energy management was modelled based on the set of transfer functions. Power converter and controller models were built in MATLAB/Simulink using block-sets. A DC-DC boost converter was chosen to step up the output DC voltage of the fuel cell and photovoltaic. Meanwhile, a bidirectional converter is used to amplify the DC voltage from the battery and to step down the magnitude of the DC voltage to the battery for charging purpose. The modelled energy management was simulated under various DC electrical loads and different source availability. The simulation results show that the system is capable to deliver optimum output power with the voltage in steady state and current within the demand tolerance range